2022
DOI: 10.1126/science.abo3034
|View full text |Cite
|
Sign up to set email alerts
|

Toward product-based regulation of crops

Abstract: Current process-based approaches to regulation are no longer fit for purpose

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Qaim (2020) suggested that a traitbased regulatory approach would represent an improvement over product-based regulation of crops. This suggestion was reiterated by Gould et al (2022).…”
Section: Sanitary and Phytosanitary Regulationsmentioning
confidence: 81%
“…Qaim (2020) suggested that a traitbased regulatory approach would represent an improvement over product-based regulation of crops. This suggestion was reiterated by Gould et al (2022).…”
Section: Sanitary and Phytosanitary Regulationsmentioning
confidence: 81%
“…As indicated by Turnbull et al (2021), the laws should not be static and must adjust according to evolving science-led knowledge based on the years of cultivating GM crops elsewhere. Although omics technology could be incorporated into the strategy for evaluating GM biofortified crops, because it allows comparing it with a non-genetically engineered cultivar (Gould et al, 2022), the analyses should give priority to the nutrient composition of the edible parts. This product-based approach depends on characteristics that are measured by advances in molecular biology.…”
Section: Bioaccessability Regulation and Acceptability Of Genetically...mentioning
confidence: 99%
“…These criteria could be used by policy makers to design a more flexible and proportionate risk assessment framework for gene edited plants. Recently, several regulatory options have been proposed ( Bratlie et al., 2019 ; Kearns et al., 2021 ; Gould et al., 2022 ). They range from maintaining the status quo (full risk assessment of genome edited organisms as GMOs) to product-based regulation or regulation based on the presence/absence of foreign DNA in the genome.…”
Section: Genome Editing Versus Traditional Genetic Modificationsmentioning
confidence: 99%